A new Approach on Mobile Phone Localization for Search and Rescue Applications - Zorn, Stefan; Rose, Richard; Götz, Alexander; Weigel, Robert (International conference on indoor positioning and indoor navigation (IPIN), 2010)
Recent statistics show an increase in environmental disasters, a fact which is also perceivable to the public as reports of avalanches, earthquakes and landslides mount in media coverage. Search and Rescue with modern localization techniques consequently attracts attention from scientific and industrial sides. This paper introduces one part of the I-LOV project, endorsed by the Federal Ministry of Education and Research Germany. Here partners from relief organizations, universities and industry investigate enhancements to disaster handling and victim rescue. One possible option is to take advantage of the fact, that a lot of people own a mobile phone today. Future developments in the area of mobile phone detection by field intensity measurements will be addressed in this paper.
elib2cris::1512001600,zorn2010
Keywords: Clocks; GSM; Phase locked loops; Protocols; Radio frequency; Universal Serial Bus